Brain Matters: Resources for Researchers in the Neurosciences. - Dorothy Barr (Issues in Science and Technology Librarianship)
The article reviews several web sites and other online resources concerning neuroscience which include the Medical Heritage Library at www.medicalheritage.org/, Human Brain Project at www.humanbrainproject.eu/ and the Society for Neuroscience at www.sfn.org/.